Pengaruh Budaya Organisasi di Lingkungan Kerja - Oktavia, Nurul; Amalia, Meila; Zahroh, Azkiatuz; O, Octavianti; Zahra, Nadya Az; S, Saridawati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
One of the key factors that influence the performance and development of an organization is its culture. A strong, positive culture can increase employee motivation, job satisfaction and productivity, while a weak culture can hinder progress and reduce effectiveness. . In the era of globalization and intensifying competition, it is important for organizations to understand how their culture can be used as a tool to create. In this study, a theoretical model that combines theories about organizational culture and theories about organizational development is used. This model identifies key cultural elements, such as values, norms, and practices, and relates them to indicators of organizational development. Overall, this analysis shows that organizational culture greatly affects organizational progress. In order to achieve the long-term goals of the organization, management must pay great attention to the establishment and maintenance of a positive culture. This is because a strong culture is essential for shaping employee behavior and creating a work environment that supports high engagement and productivity. Organizations can create a dynamic and productive work environment by concentrating on developing visionary leadership, improving internal communication, and increasing employee engagement. This will drive innovation, improve operational efficiency, and ensure well-being.